Phase I/II randomized, double-masked, placebo-controlled study of processed amniotic fluid drops after PRK. Issue 3 (March 2023) - Ip, Colin S.; Jones, D. Kyle; Weinlander, Eric; Gudgel, Brett; Lin, Amy; Yazdani, Hina; Pierce, Jan; Holubkov, Richard; Jensen, Hailey; Church, Myrna; Mifflin, Mark D.
Abstract : Processed amniotic fluid (pAF) did not improve time to full re-epithelialization after PRK compared to placebo. pAF can be safely used for other ophthalmic applications. Abstract : Purpose: To evaluate the safety and efficacy of processed amniotic fluid (pAF) used postoperatively after photorefractive keratectomy (PRK). Setting: University of Utah, Moran Eye Center, Salt Lake City, Utah. Design: Randomized, double-masked, placebo-controlled prospective study. Methods: 61 participants were randomized to receive either placebo or pAF drops, which were instilled 4 times per day for 1 week after PRK along with routine postoperative medications. The primary outcome measure was time to full re-epithelialization in days. Secondary measures included visual acuity at 30 days and postoperative pain scores during the first week. Results: There was no significant difference in time to re-epithelialization, with a median of 5 days for both groups. There were no difference in pain indicator scores during the first week and no difference in corneal staining scores at day 30 between the 2 groups. There were no adverse events. Conclusions: This pilot study evaluating the safety and efficacy of pAF as an additional postoperative topical medication for PRK demonstrated that pAF did not improve the rate of epithelial healing after PRK. pAF may be safely studied in other ocular conditions to determine its effect on epithelial healing.